Endoscopic ultrasound-guided puncture suture device versus metal clip for gastric defect closure after endoscopic full-thickness resection: A randomized, comparative, porcine study - Sun, Beibei (Endosc Ultrasound, 2016)
OBJECTIVE: The secure closure of the wall defect is a critical stage of endoscopic full-thickness resection (EFTR). The aim of this study was to compare the closure of post-EFTR defects using an endoscopic ultrasound-guided puncture suture device (PSD) with the metal clip (MC) technique in a randomized, comparative, porcine study. METHODS: We performed a randomized comparative survival study that included 18 pigs. The circular EFTR defects with a diameter of approximately 20 mm were closed with either a PSD or MC. Serum levels of interleukin-6 (IL-6) were determined preoperatively and on a postoperative day (POD) 1, 3, and 7. Three animals from each group were sacrificed at the end of the 7(th), 14(th), and 30(th) POD. Tissue samples retrieved from the closure sites were examined macroscopically and microscopically. RESULTS: Resection and closure were performed in 18 pigs (100%) without major perioperative complications. The mean closure time was significantly longer in the MC group than in the PSD group (25.00 ± 3.16 min vs. 1.56 ± 0.39 min; P < 0.05). Preoperative and POD 7 serum levels of IL-6 did not differ between the two groups. However, on POD 1, the IL-6 levels were observed to be significantly greater in the MC group than in the PSD group (P < 0.005). No significant differences between the PSD and MC groups were observed at necropsy. CONCLUSION: In this in vivo porcine model, PSD is a feasible device that achieves post-EFTR defect closure with a much shorter closure time and with less immunological responses than the MC technique.